HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP IBU HAMIL RESIKO TINGGI USIA MUDA (14-20 TAHUN) DI WILAYAH KERJA PUKESMAS BANDAR KECAMATAN BANDAR KABUPATEN BENER MERIAH TAHUN 2023 - Mah Bengi, Julita; Hudnah; HS, Nurlaely (Jurnal Ilmiah Cerebral Medika, 2024)
ABSTRACTMaternal mortality rate (MMR) is a health problem for pregnant women in Indonesia,including in Bener Meriah Regency, Aceh Province in 2023. Data in Aceh province put the risk of death during pregnancy and childbirth at around 201/100,000 births. This study aims to analyze the relationship between knowledge and attitudes of young pregnant women (14-20 years) with high-risk events in pregnant women in the working area of Pukesmas Bandar, bandar district, bener meriah regency in 2023. The type of research used is quantitative and cross-sectional design. with a total sample of 48 pregnant women in the Pukesmas Working Area of the city, city sub-district. The results showed that the characteristic variables of pregnant women had significant knowledge with variables of high-risk events in pregnant women at a significant level of 0.003, attitudes with variables of high-risk events in pregnant women at a significant level of 0.003. These results conclude that there is a relationship between knowledge and attitudes with high-risk pregnancies in pregnant women in the Pukesmas Bandar Working Area, Bandar District. It is recommended to government institutions in Bener Meriah district to intensely conduct counseling to the community, especially about the high risk for pregnant women by often giving to pregnant women about the dangers of high risk during pregnancy or conducting health checks for pregnant women. Keywords : The Incidence of Resti, Young Pregnant Women